AB1057 Contextualisation of Safety Endpoints in the Tofacitinib Rheumatoid Arthritis (RA) Development Programme: Collaboration with the Consortium of Rheumatology Researchers of North America (CORRONA) Registry. (10th June 2014) - Geier, J.; Saunders, K.; Reed, G.
Abstract : Background: Epidemiological data are needed throughout the product's life cycle to contextualise safety findings particularly when interpretation of adverse events (AEs) is not feasible within clinical trial data (i.e., insufficient statistical power, lack of active comparator, paucity of quality published data). Objectives: To develop a cohort of patients with RA with similar characteristics (i.e., demographics and disease severity) to patients within the tofacitinib global Phase 2, Phase 3 and long-term extension RA studies to: 1) estimate the baseline comorbidities within 3 cohorts of patients with RA; 2) quantify the background incidence of known and potential tofacitinib safety concerns in an RA population; and 3) quantify the background incidence of new potential safety concerns as they arise in an RA population. Methods: Pfizer Inc collaborated with the CORRONA registry to establish 3 unique cohorts of patients to query for safety contextualisation: 1) all patients with RA; 2) patients with moderate to severe RA (operationalised as ≥4 Joint Count and American College of Rheumatology functional class of I, II or II); and 3) patients with moderate to severe RA with at least one cardiovascular risk factor. The primary outcomes of interest included serious infections, malignancies and cardiovascular endpoints as reported by physicians. To calculate the rate of each safety event, the number of incident events was divided by the total person-years of observation within the eligible RA cohort. Results: Over 22, 000 adult patients with RA with at least one follow-up visit were identified within the registry. Overall, the rate of AEs was higher among the cohort of patients with moderate to severe disease relative to the total RA population and among patients who were ≥65 years of age relative to those <65 (Figure). Conclusions: Expected rates of many identified and potential risks were estimated in various RA cohorts, allowing comparison with rates from the tofacitinib clinical trial programme. The results of this collaboration allowed for feasibility assessments for post-marketing studies, rapid analyses of safety events, and rate stratification by background comorbidities. Given the coverage of the CORRONA registry, these data are generalisable to the general US RA population. Acknowledgements: This study is sponsored by CORRONA. In the past 2 years, AbbVie, Amgen, AstraZeneca, Genentech, Horizon Pharma, Eli Lilly, Novartis, Pfizer, Vertex and UCB have supported CORRONA through contracted subscriptions. Medical writing support was provided by CMC, funded by Pfizer Inc. Disclosure of Interest: J. Geier Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, K. Saunders Employee of: CORRONA Inc., G. Reed Employee of: CORRONA Inc. DOI: 10.1136/annrheumdis-2014-eular.2474